Warts: A Comprehensive Overview (Homoeopathy for All, 2024)
Warts, benign skin growths caused  by the human papillomavirus  (HPV), are a widespread  dermatological condition affecting  individuals worldwide. These  growths are notably prevalent, with  global estimates suggesting that  around 10% of children and 1-5%  of adults experience warts at some  point in their lives. The frequency  of warts varies by age, lifestyle, and  environmental conditions. Children  and adolescents, in particular, are  at higher risk due to frequent skin to-skin contact in settings such as  schools and sports. Additionally,  regions with warm and humid  climates often report higher rates of  HPV transmission, contributing to  increased wart prevalence.
Keywords: environmental; dermatological condition; HPV